2012
DOI: 10.1016/j.neuroimage.2011.11.062
|View full text |Cite
|
Sign up to set email alerts
|

Somatosensory activation of two fingers can be discriminated with ultrahigh-density diffuse optical tomography

Abstract: Topographic non-invasive near infrared spectroscopy (NIRS) has become a well-established tool for functional brain imaging. Applying up to 100 optodes over the head of a subject, allows achieving a spatial resolution in the centimeter range. This resolution is poor compared to other functional imaging tools. However, recently it was shown that diffuse optical tomography (DOT) as an extension of NIRS based on high-density (HD) probe arrays and supplemented by an advanced image reconstruction procedure allows de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
73
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(73 citation statements)
references
References 58 publications
0
73
0
Order By: Relevance
“…• Some devices offer interfaces to allow for multi-modal imaging and have successfully been used for example in simultaneous measurements of fNIRI and MEG (Seki et al, 2012), EEG (Hebden et al, 2012;Leamy and Ward, 2010), fMRI (Habermehl et al, 2012a;Toronov et al, 2001;X. Zhang et al, 2005) and other modalities.…”
Section: Overview Of Commercially Available Imaging Instrumentationmentioning
confidence: 99%
“…• Some devices offer interfaces to allow for multi-modal imaging and have successfully been used for example in simultaneous measurements of fNIRI and MEG (Seki et al, 2012), EEG (Hebden et al, 2012;Leamy and Ward, 2010), fMRI (Habermehl et al, 2012a;Toronov et al, 2001;X. Zhang et al, 2005) and other modalities.…”
Section: Overview Of Commercially Available Imaging Instrumentationmentioning
confidence: 99%
“…Continuous-wave DOT reconstructs the distribution of the changes in optical properties inside the tissue from the changes in measured light intensity using knowledge of the spatial information of the optical paths of measurement channels [6,[19][20][21][22]. In our previous study, we proposed a three-dimensional reconstruction method with high spatial resolution in both the depth and horizontal directions [23], where we introduced sparse regularization to improve the depth accuracy and the spatial resolution.…”
Section: Introductionmentioning
confidence: 99%
“…The most striking result is that although it has been shown that geometric surface error (and hence) sensitivity error (light propagation error) can be substantial depending on different types of registration algorithms, no single algorithm is providing errors greater than 4.5 mm in location error. This is perhaps expected as in most functional DOT imaging experiments, we are concerned with dynamic (often referred to temporal or difference) imaging, whereby rather than recovering an absolute image of optical properties, we are only concerned with recovery of changes with respect to a baseline and this type of image recovery has shown to be less prone to geometric and model errors as compared to static (absolute) imaging [14,47,48]. The relative overlay depends (as expected) on the threshold value and is closer to the expected 100% using the 70% threshold.…”
Section: Resultsmentioning
confidence: 99%
“…While most hemodynamic-based neuroimaging research studies in adult subjects are typically performed using functional magnetic resonance imaging (fMRI), its relative high cost, fixed scanner locations and physical constraints during imaging, limit fMRI's translation as a bedside clinical tool [10]. DOT has shown a strong potential in clinical application specifically for neonate and long-term bedridden patients [11] and NIR studies of the human brain have demonstrated its ability to recover abnormalities as haemorrhage detection from stroke patients [12] with accurate recovery of stimulated activations [13][14][15] and functional networks [5,16,17].…”
Section: Introductionmentioning
confidence: 99%